Análise comparativa do desempenho mecânico de ligas β-Ti em implantes ortopédicos como alternativas aos biomateriais metálicos comerciais - Jose, Gustavo Alves (2022)
According to the World Health Organization, the life expectancy of the population is increasing, in this context, the number of interventions for the implementation of orthopedic implants in the human body also grows over the decades. Thus, it becomes necessary to develop materials with high biocompatibility with the human body. In this context, some of the commercial metallic biomaterials currently used for this type of application, such as commercially pure titanium, the Ti-6Al-4V alloy, Co-Cr-Mo alloys and Stainless Steels, have a Modulus of Elasticity value higher than the value of human bone. In addition, some of these materials still have cytotoxic elements in their composition, such as aluminum, which can cause neurological diseases such as Alzheimer's from the release of harmful ions to the human body in the long term. Thus, this monograph performs the survey of microstructural and mechanical data of different β-titanium alloys with biocompatible alloying elements in their composition in order to ascertain whether the microstructural change of these materials provided more suitable mechanical properties for application in orthopedic implants. Thus, microstructural data of different alloys of the Ti-Mo, Ti-Nb, TNZT and TMZF systems were collected from optical microscopy and X-ray diffraction analysis (DRX), in addition to the mechanical properties of modulus of elasticity, Vickers hardness , Yield stress, elongation and tensile strength limit. From the results obtained, the metallic alloy of the TNZT system presented a Modulus of Elasticity closer to the desired value for this type of application 56 GPa, however, all the β alloys surveyed presented Modulus of Elasticity lower than those of Commercial Metallic Biomaterials. In addition, with regard to tensile and hardness properties, the TMZF system proved to be the best material with yield strength, tensile strength and hardness values equal to, respectively, 1030 MPa, 1080 MPa and 345 HV. In general, the raised β alloys showed superior mechanical properties to commercial biomaterials, making it necessary to carry out studies that analyze the fatigue properties of these alloys in addition to the economic viability of their large-scale implementation of these materials.